Depression, anxiety, and stress mediate the associations between internet gaming disorder, insomnia, and quality of life during the COVID-19 outbreak. (December 2020) - Fazeli, Sara; Mohammadi Zeidi, Isa; Lin, Chung-Ying; Namdar, Peyman; Griffiths, Mark D.; Ahorsu, Daniel Kwasi; Pakpour, Amir H.
Highlights: Depression, anxiety, and stress mediates the association between internet gaming disorder and insomnia. Depression, anxiety, and stress mediates the association between internet gaming disorder and quality of life. Internet gaming disorder may have multiple pathways in affecting adolescents' sleep and quality of life. Abstract: Background: For many individuals, the COVID-19 outbreak has increased their psychological distress, changed their behaviors, and impacted their health. With more time spent indoors, many individuals have engaged in increased videogame playing. However, the associations between such behaviors during the COVID-19 outbreak period is unclear. Objective: The present study examined the mediating role of psychological distress (depression, anxiety, and stress) in the association between internet gaming disorder (IGD) and two health outcomes (insomnia quality of life) among adolescents during this COVID-19 pandemic. Methods: A cross-sectional study comprising adolescents ( N = 1512) aged 13–18 years (mean age = 15.51 years) was utilized to assess measures on insomnia, depression, anxiety, and stress, IGD, and quality of life during the COVID-19 pandemic. Results: There were small to large significant relationships between the variables. Psychological distress (i.e., depression, anxiety, and stress) served as a strong mediator in the association between IGD and insomnia and quality of life. IGD directly influenced insomnia and quality of life among the participants. Conclusions: IGD is associated with different psychosocial outcomes comprising multiple pathways. Parents need to pay special attention to how much time and how frequently their children play videogames. Parents may need to assist their children in coping with psychological distress during the ongoing COVID-19 pandemic period.